A 3D Laboratory Test-Platform for Overhead Power Line Inspection. (19th April 2016) - Liu, Chang-An; Dong, Ruifang; Wu, Hua; Yang, Guo-Tian; Lin, Wei
Using unmanned aerial vehicles (UAVs) for performing automatic inspection of overhead power lines instead of foot patrols is an attractive option, since doing so is safer and have considerable cost savings, among other advantages. The purpose of this paper is to design a 3D laboratory test-platform to simulate UAVs' inspection of transmission lines and secondly, proposing an automated inspection strategy for UAVs in order to follow transmission lines. The construction and system architecture of our 3D test-platform is described in this paper. The inspection strategy contributes to knowledge pertaining to an automated inspection procedure and includes two steps: flight path planning for UAVs and visual tracking of the transmission lines. The 3D laboratory test-platform is applied to test the performance of the proposed strategy and the tracking results of our inspection strategy are subsequently presented. The availability of the 3D laboratory test-platform and the efficiency of our tracking algorithm are verified by experiments.